Assessing locally-led anticipatory action options to counter climate-induced humanitarian crises in East Africa - Tsitati, George (Jameel Observatory for Food Security Early Action, 2024)
Presented at Jameel Observatory for Food Security Early Action Community of Practice meeting, Nairobi, 14-15 May 2024